2023
DOI: 10.3390/ijms24076499
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental and Epigenetic Changes on Mesenchymal Stem Cells during Aging

Abstract: Many crucial epigenetic changes occur during early skeletal development and throughout life due to aging, disease and are heavily influenced by an individual’s lifestyle. Epigenetics is the study of heritable changes in gene expression as the result of changes in the environment without any mutation in the underlying DNA sequence. The epigenetic profiles of cells are dynamic and mediated by different mechanisms, including histone modifications, non-coding RNA-associated gene silencing and DNA methylation. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 209 publications
0
3
0
Order By: Relevance
“…Mounting evidence has shown that epigenetic regulation, including histone modifications, chromatin remodeling, and DNA methylation, are commonly associated with the MSC aging process and may contribute to MSC senescence-related manifestation. 21 , 22 , 23 For example, histone deacetylases (HDACs) mediate self-renewal of MSCs by balancing polycomb group genes and lysine demethylase 6B (KDM6B) expression. 24 It has been shown that upregulation of miR-155-5p lead to elevated cell senescence, while downregulation of miR-155-5p reduce MSC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence has shown that epigenetic regulation, including histone modifications, chromatin remodeling, and DNA methylation, are commonly associated with the MSC aging process and may contribute to MSC senescence-related manifestation. 21 , 22 , 23 For example, histone deacetylases (HDACs) mediate self-renewal of MSCs by balancing polycomb group genes and lysine demethylase 6B (KDM6B) expression. 24 It has been shown that upregulation of miR-155-5p lead to elevated cell senescence, while downregulation of miR-155-5p reduce MSC senescence.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that CVRFs have long term effects on circulating EPCs, or even their stem cell precursors (Figure 4). The underlying mechanisms may include epigenetic changes [261,262] as well as covalent modifications of cell components, i.e., oxidative damage of biomolecules, including proteins and lipids, which may lead to potentially irreversible and adverse consequences [263]. Additionally, oxidative DNA damage can induce either permanent genetic or epigenetic changes [264], that might be passed on daughter cells through cell division.…”
Section: Endothelial Progenitor Cells and Cardiovascular Risk Factors...mentioning
confidence: 99%
“…Inducing profound changes in epigenetics may be an underlying factor of the beneficial effects of exercise. The effects of exercise on total DNA methylation in various tissues, including skeletal muscle, adipose tissue and blood, have been demonstrated in many studies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%